IMPROVEMENT OF RESULTS OF KIDNEY TRANSPLANTATION - A. G. Stolyar; L. N. Budkar; N. F. Klimusheva; O. M. Lesnjak (Вестник трансплантологии и искусственных органов, 2014)
Aim. Analysis of the results of kidney allotransplantations over 20 years (1990–2010), made by the research group from the Regional Hospital № 1 (Ekaterinburg, Russia).Materials and methods. We analyzed the outcomes of kidney transplantations in 340 patients: men – 218 (64%), women – 122 (36%), average age: 12 to 61(37,57 ± 0,64). We focused on the patient and transplant survival rates, structure of mortality and transplant loss. For the statistical analysis we used SPSS.Results. Patient survival rate during 10-year period was 64%; transplantsurvival rate during 10-year period was 48%. Patient survival rate during 20-year period was 43%; transplant survival rate during 20-year period was 41%. The main causes of patients’ death were infections; the dominant causes of transplant losses were deaths of patients with functioning transplants and chronic allograft nephropathy. We defi ned statistically reliable improvement of transplant results over last 10 years. We showed the advantages of molecular genetic method of immunological selection of donor-recipient pair for improvement of transplant outcomes. Conclusion. Over last 10 years we observed an improvement of kidney allograft results by means of contemporary methods of immunosuppressive therapy, immunological selection of transplants and other factors.